Analysis of Spanish Parents’ Knowledge about ASD and Their Attitudes towards Inclusive Education - Irene Gómez-Marí; Raúl Tárraga-Mínguez; Gemma Pastor-Cerezuela (European Journal of Investigation in Health, Psychology and Education, 2022)
To make possible the inclusion of children with autism spectrum disorder (ASD) in mainstream settings, parental knowledge and attitudes towards the disorder play a key role between the home and the school setting. However, prior literature has not carried out an in-depth analysis of parents’ knowledge about ASD and their attitudes toward the inclusion of children with this diagnosis. This study examined the parental attitudes towards inclusion and knowledge about ASD. Participants were parents of children with ASD (n = 75), parents of children without ASD whose children had prior or current contact with peers with ASD (n = 44), and parents of children with no previous interactions with a peer with ASD (n = 51). The Attitudes of Regular Educators Towards Inclusion for Students with Autism Survey and the Autism Knowledge Questionnaire were filled out. Nonparametric statistical tests were used. Results showed that parents of children with ASD have better knowledge about this disorder and hold more favorable attitudes towards the inclusion of children with ASD than the other parents. These findings suggest that the benefits of inclusive schooling are limited to the school setting and do not appear to affect families of children without ASD.